Spanish in New York language contact, dialectal leveling, and structural continuity - Otheguy, Ricardo, 1945-; Zentella, Ana Celia (New York : Oxford University Press, 2012)
Spanish in New York is a groundbreaking sociolinguistic analysis of immigrant bilingualism in a U.S. setting. Drawing on one of the largest corpora of spoken Spanish ever assembled for a single city, Otheguy and Zentella demonstrate the extent to which the language of Latinos in New York City represents a continuation of structural variation as it is found in Latin America.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Spanish language -- Provincialisms -- New York (State) -- New York; Spanish language -- Pronoun; Spanish language -- Dialects -- New York (State) -- New York; Bilingualism -- New York (State) -- New York